Polyethylene composition and production method thereof

By using metal luster catalysts in the gas phase aggregation system to prepare polyethylene closer, solve the problem of high melt viscosity in the squeezing process of the existing MLLDPE resin, realize the balance of melt intensity and processability, and reduce production costs.

CN119343383APending Publication Date: 2025-01-21EXXONMOBIL CHEMICAL PATENTS INC
View PDF 15 Cites 0 Cited by

Patent Information

Application Number
CN202380041070.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-18
Filing Date
2023-03-28
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The existing low melt index and high molecular weight mLLDPE resins have high pressure and high motor loads due to high melt viscosity during the extrusion process, and it is difficult to improve processability and reduce production costs.

Method used

By using a metallocene catalyst in a gas phase polymerization system, a polyethylene copolymer with a density between 0.908g/cm3 to 0.916g/cm3 and a melt index I2 of 0.10g/10min to 0.60g/10min and greater than or The melt index ratio I21/I2 is equal to 46.9-(33.3×(I2)).

Benefits of technology

Achieving a balance of melt strength and processability of polyethylene copolymers, reducing extruder pressure and motor load, improving production efficiency and reducing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005138597800000251
    Figure BDA0005138597800000251
  • Figure BDA0005138597800000261
    Figure BDA0005138597800000261
  • Figure BDA0005138597800000262
    Figure BDA0005138597800000262
Patent Text Reader

Abstract

Polyethylene copolymers having an improved balance of melt strength and processability and methods of making such polyethylene copolymers are provided. In some embodiments, the polyethylene copolymer comprises from 9 to 11 wt% of at least one comonomer containing from 4 to 8 carbon atoms, and has a density of from 0.908 to 0.916 g / cm3, a melt index I2 of from 0.10 to 0.60 g / 10 min, and a melt index ratio I21 / I2 of greater than or equal to 46.9-(33.3 x (I2)), where I2 is provided in g / 10 min. In some embodiments, the polyethylene copolymer is produced in a dry mode gas phase process using a metallocene catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Cross reference to related cases

[0001] This application claims the benefit of U.S. Provisional Application No. 63 / 364,923, filed on May 18, 2022, entitled “Polyethylene Compositions and Methods for Producing The Same,” the entire contents of which are incorporated herein by reference. Technical Field

[0002] The present disclosure relates to polyethylene copolymers, polymerization processes for preparing such polyethylene copolymers, and products comprising such polyethylene copolymers. Background Art

[0003] Low melt index, high molecular weight polymers are often used in applications such as stretch hoods, greenhouse films, and building linings because they have the necessary melt strength to support the large melt bubbles formed during blown film processing. Compared to current alternatives, lower density metallocene-based linear low density polyethylene ("mLLDPE") resins provide excellent toughness and optical properties for such applications. However, current low melt index, high molecular weight mLLDPE resins have high melt viscosities, which may impose processability limitations due to high melt viscosities, in addition to producing high pressures and high motor loads in the extruder. It would be desirable to have a low density, high molecular weight mLLDPE resin that has high toughness and clarity, yet has a lower melt viscosity, thereby allowing for improved processability and reduced production costs via lower extruder pressures and corresponding motor load reductions.

[0004] WO publication WO2021 / 221904 discloses a density of 0.931 to 0.936 g / cm 3 Polyethylene copolymers exhibiting improved stress crack resistance, methods for preparing such copolymers using metallocene catalysts, and films prepared from such copolymers. The polyethylene copolymers include at least 95 weight percent ethylene and up to 5 weight percent of at least one comonomer containing 3 to 18 carbon atoms, and have a 30% single point notch constant tensile load of at least 1,000 hours. It is suggested that reducing the concentration of the induced condensing agent can result in an increase in the amount of comonomer incorporated into the higher molecular weight polymer chain, thereby resulting in a desired balance of properties.

[0005] Recent articles disclose the use of metallocene catalysts to produce 3The article points out that mLLDPE resin exhibits excellent dart impact, puncture toughness, high transparency, low seal initiation temperature and good softness, and can be used in many blown film applications. The article shows that the improved performance of mLLDPE resin is due to a small amount of long chain branching. See "Novelmetallocene-based linear low density polyethylene (LLDPE) for blown film applications", IP.com Prior Art Database Technical Disclosure, IP.com Publication No.: IPCOM000266833D, IP.com Electronic Publication Date: August 25, 2021.

[0006] Another recent article discloses the use of induced condensing agents to control density to 0.910 to 0.960 g / cm 3 The rheology and melt strength of ethylene-butene mLLDPE were studied, showing that increasing the induced condensing agent by 10 to 18 mol% during gas phase polymerization resulted in improved melt strength. Increasing the concentration of the induced condensing agent during polymerization also produces resins with higher comonomer content in the lower molecular weight polymer chains relative to the comonomer content in the higher molecular weight polymer chains. See "Induced Condensing Agent Control for Tunable Linear Low Density Polyethylene Properties during Gas Phase Polymerization with Transition Metal Catalyst Systems," IP.com Prior Art Database Technical Disclosure, IP.com No.: IPCOM000268060D, IP.com Electronic Publication Date: December 20, 2021.

[0007] There remains a need for a low density, high molecular weight polyethylene having a balance of melt strength, processability, toughness and clarity that is suitable for producing certain products using a blown film process. A valuable method for producing such a polymer would avoid expensive additives and performance compromises. Ideally, an improved mLLDPE composition could be prepared using economical starting materials, conventional equipment and familiar techniques. Summary of the invention SUMMARY OF THE INVENTION

[0008] The present disclosure provides polyethylene copolymers comprising units derived from ethylene and at least one olefin comonomer containing from 4 to 8 carbon atoms and having an improved balance of melt strength and processability.

[0009] In some embodiments, the polyethylene copolymer has: a)0.908g / cm 3 Up to 0.916g / cm 3 density; b) a melt index I2 of 0.10 g / 10 min to 0.60 g / 10 min; and c) a melt index ratio I greater than or equal to 46.9-(33.3×(I2)) 21 / I2, where I2 is provided in g / 10min.

[0010] In some embodiments, in addition to the foregoing attributes, the polyethylene copolymer has a comonomer content of 9.0 wt% to 11.0 wt%.

[0011] In some embodiments, the comonomer is 1-hexene, and the polyethylene copolymer has a melt index I2 of 0.10 g / 10 min to 0.30 g / 10 min and a melt index ratio I2 of greater than or equal to 45.1. 21 / I2 ("MIR"), or a melt index I2 of 0.40 g / 10 min to 0.60 g / 10 min and a melt index ratio I greater than or equal to 35.1 21 / I2.

[0012] In some embodiments, the polyethylene copolymer is produced in a continuous gas phase process comprising: a) continuously passing a gaseous stream comprising ethylene and at least one olefin comonomer having from 4 to 8 carbon atoms through a fluidized bed reactor in the presence of a metallocene catalyst under polymerization conditions, wherein the polymerization conditions include an ethylene partial pressure greater than, or equal to, 1300 kPaa and a reactor pressure less than, or equal to, 10,000 kPag; b) extracting the polyethylene copolymer and a stream comprising unreacted ethylene, unreacted comonomer, and optionally an induced condensing agent, wherein the induced condensing agent comprises less than 5 mole percent of the stream; c) cooling the stream comprising unreacted ethylene, unreacted comonomer, and an induced condensing agent to form a cooled stream, wherein the cooled stream is substantially free of a liquid phase; and d) feeding the cooled stream to the fluidized bed reactor along with sufficient additional ethylene and at least one comonomer to replace the ethylene and at least one comonomer polymerized and extracted as the polyethylene copolymer.

[0013] The foregoing has been quite extensively summarized the features and technical advantages of the present invention so that the subsequent detailed description of the present invention can be better understood. Additional features and advantages of the present invention will be described hereinafter, which form the subject matter of the claims of the present invention. It should be appreciated by those skilled in the art that the disclosed concepts and specific embodiments can be easily used as improvements or designs for membrane structures and / or other methods for carrying out the same purpose of the present invention. It should also be recognized by those skilled in the art that these equivalent constructions do not depart from the spirit and scope of the present invention listed in the appended claims. The novel features (both about its structure and manufacturing method) and further objects and advantages that are considered to be features of the present invention will be better understood from the following description. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] The claimed subject matter may be understood by reference to the following description taken in conjunction with the accompanying drawings, in which like reference numerals identify like elements, and in which:

[0015] Figure 1 is an overlay of weight fraction versus molecular weight of a polyethylene copolymer having a melt index I2 of about 0.2 g / 10 min according to an embodiment of the present technology compared to prior art copolymers;

[0016] Figure 2 is an overlay of weight fraction versus molecular weight of a polyethylene copolymer having a melt index I2 of about 0.5 g / 10 min according to an embodiment of the present technology compared to prior art copolymers;

[0017] Figure 3 is an overlay of comonomer content versus molecular weight for a polyethylene copolymer having a melt index I2 of about 0.2 g / 10 min according to an embodiment of the present technology compared to prior art copolymers;

[0018] Figure 4 is an overlay of comonomer content versus molecular weight for a polyethylene copolymer having a melt index I2 of about 0.5 g / 10 min according to an embodiment of the present technology compared to prior art copolymers;

[0019] Figure 5 is an overlay of branching index versus molecular weight for a polyethylene copolymer having a melt index I2 of about 0.2 g / 10 min according to an embodiment of the present technology compared to prior art copolymers;

[0020] Figure 6 is an overlay of branching index versus molecular weight for a polyethylene copolymer having a melt index I2 of about 0.5 g / 10 min according to an embodiment of the present technology compared to prior art copolymers;

[0021] Figure 7is an overlay of phase angle versus complex modulus for a polyethylene copolymer having a melt index I2 of about 0.2 g / 10 min according to embodiments of the present technology compared to prior art copolymers; and

[0022] Figure 8 is an overlay of phase angle versus complex modulus for a polyethylene copolymer having a melt index I2 of about 0.5 g / 10 min according to embodiments of the present technology compared to prior art copolymers.

[0023] Although the disclosed method and system are susceptible to various modifications and alternative forms, the accompanying drawings show by way of example specific embodiments described in detail herein. However, it should be understood that the description of specific embodiments herein is not intended to limit the invention to the specific forms disclosed, but on the contrary, it is intended to cover all modifications, equivalents and alternatives falling within the spirit and scope of the invention defined by the appended claims. DETAILED DESCRIPTION OF THE INVENTION

[0024] Illustrative embodiments of the subject matter claimed below will now be disclosed. For the sake of clarity, some features of some actual implementations may not be described in this specification. It should be understood that in the development of any such actual implementation, many implementation-specific decisions must be made to achieve the developer's specific goals, such as compliance with system-related and business-related constraints, which will vary from one implementation to another. In addition, it should be understood that such development work, even if complex and time-consuming, is a routine task for those of ordinary skill in the art who benefit from the present disclosure.

[0025] The words and phrases used herein should be understood and interpreted as having a meaning consistent with the understanding of such words and phrases by those skilled in the relevant art. Any special definition of a term or phrase, i.e., a definition that is different from the ordinary and customary meaning as understood by those skilled in the art, is not intended to be implied by consistent use of the term or phrase herein. To the extent a term or phrase is intended to have a special meaning (i.e., a meaning other than the broadest meaning as understood by those skilled in the art), such special or clarified definition will be clearly set forth in the specification in a manner that provides a special or clarified definition for the term or phrase.

[0026] For example, the following discussion contains a non-exhaustive list of definitions of several specific terms used in this disclosure (other terms may be defined or clarified in definitions elsewhere herein). These definitions are intended to clarify the meaning of the terms used herein. It is believed that these terms are used in a manner consistent with their ordinary meanings, but for clarity, the definitions are still specified here. definition

[0027] As used herein, "C n", unless otherwise indicated, the term refers to hydrocarbon(s) containing n carbon atoms(s) per molecule, where n is a positive integer.

[0028] As used herein, "free of" a component means that the composition is substantially free of the component, or comprises the component in an amount of less than about 0.01 wt %, based on the weight of the total composition.

[0029] As used herein, "olefins", or "olefins", are linear, branched or cyclic compounds of carbon and hydrogen having at least one double bond. For purposes of this specification and the claims thereto, when a polymer or copolymer is referred to as "comprising" an olefin, the olefin present in such polymer or copolymer is the polymerized form of the olefin. For example, when a copolymer is described as having an "ethylene" content of 35% to 55% by weight, it is understood that the monomer units in the copolymer are derived from ethylene in the polymerization reaction, and the derived units are present at 35% to 55% by weight, based on the weight of the copolymer.

[0030] As used herein, "polyethylene copolymer" refers to a polymer or copolymer comprising at least 89% by weight ethylene. The terms "polyethylene polymer", "polyethylene", "ethylene polymer", "ethylene copolymer" and "ethylene-based polymer" have the same meaning as polyethylene copolymer, unless otherwise indicated (e.g., in the case of reference to polyethylene homopolymers, this means a polymer formed from ethylene monomers without comonomer units, e.g., 100% by weight ethylene-derived units).

[0031] As used herein, "polymerization conditions" refers to conditions that facilitate the reaction of one or more olefin monomers to produce a polyolefin polymer when contacted with an activated olefin polymerization catalyst, and includes the selection by one skilled in the art of temperature, pressure, reactant concentrations, optional solvents / diluents, reactant mixing / addition parameters, and other conditions within at least one polymerization reactor.

[0032] For the sake of simplicity, only some numerical ranges are clearly disclosed herein. However, in addition to the ranges listed, any lower limit can be combined with any upper limit to list the range that is not clearly listed, and the range starting from any lower limit can be combined with any other lower limit to list the range that is not clearly listed, and in the same way, the range starting from any upper limit can be combined with any other upper limit to list the range that is not clearly listed. In addition, even if there is no clear description, each point or individual value between the two end points is also included in the scope. Therefore, each point or individual value itself can be used as a lower limit or upper limit in combination with other points or individual values ​​or other lower or upper limits to limit the range that is not clearly recorded. Polyethylene copolymer

[0033] The polyethylene copolymer provided herein comprises or consists of units derived from ethylene and at least one olefin comonomer containing 4 to 8 carbon atoms, and has a molecular weight of 0.908 g / cm 3 Up to 0.916g / cm 3 density, a melt index I2 of 0.10 g / 10 min to 0.60 g / 10 min, and a melt index ratio I greater than or equal to 46.9-(33.3×(I2)) 21 / I2 (where I2 is provided in g / 10min), and a branching index g'vis (LCB index, also referred to as g'(vis) or g' index) of 0.940 to 0.960, thereby reflecting a measurable (even if small) degree of long chain branching. The polyethylene copolymers described herein have an improved balance of melt strength, processability (e.g., reduced melt viscosity), toughness, and clarity, making them suitable for producing certain products using a blown film process.

[0034] The polyethylene copolymer may have a melt index ratio I greater than or equal to 51.8-(33.3×(I2)), 52.8-(33.3×(I2)), or greater than or equal to 55.1-(33.3×(I2)). 21 / I2, where I2 is provided in g / 10min.

[0035] The polyethylene copolymer may have a comonomer content of 9.0 wt % to 11.0 wt %. In some embodiments, the comonomer is selected from butene, hexene, or a combination thereof. In some embodiments, the comonomer is 1-butene. In some embodiments, the comonomer is 1-hexene.

[0036] The density of polyethylene copolymer can be ((0.0025×W)+(0.0056×*I2)+0.9353)g / cm 3 ±0.001g / cm 3 In various embodiments, the polyethylene copolymer has a melt index I2 of 0.10 g / 10 min to 0.30 g / 10 min and a melt index I2 of 0.908 g / cm 3 Up to 0.915g / cm 3 , 0.909g / cm 3 Up to 0.914g / cm 3 or 0.910g / cm 3 Up to 0.913g / cm 3 In some embodiments, the polyethylene copolymer has a melt index I2 of 0.40 g / 10 min to 0.60 g / 10 min and a 3Up to 0.916g / cm 3 、0.911g / cm 3 Up to 0.915g / cm 3 or 0.912g / cm 3 Up to 0.914g / cm 3 density.

[0037] The polyethylene copolymer may have a weight average molecular weight M in the range of ((2,900×W)-(63,500×I2)+110,300) g / mol±1,000 g / mol, ±2,000 g / mol, or ±5,000 g / mol. w , wherein W is the weight percent of the comonomer incorporated into the polyethylene copolymer and I2 is provided in g / 10 min. In some embodiments, the polyethylene copolymer has a melt index I2 of 0.10 g / 10 min to 0.30 g / 10 min and a weight average molecular weight M of 117,400 g / mol to 135,900 g / mol, 120,300 g / mol to 133,000 g / mol, 120,600 g / mol to 132,700 g / mol, or 123,200 g / mol to 130,100 g / mol. w In some embodiments, the polyethylene copolymer has a melt index I2 of 0.40 g / 10 min to 0.60 g / 10 min and a weight average molecular weight M of 98,300 g / mol to 116,800 g / mol, 101,200 g / mol to 133,900 g / mol, 101,500 g / mol to 113,700 g / mol, or 104,100 g / mol to 111,000 g / mol. w .

[0038] The polyethylene copolymer may have a Z average molecular weight Mz in the range of ((2,360×W)-(125,900×I2)+252,000) g / mol±500 g / mol, ±1000 g / mol, or ±2,500 g / mol, wherein W is the weight percent of the comonomer incorporated into the polyethylene copolymer and I2 is provided in g / 10 min. In some embodiments, the polyethylene copolymer has a melt index I2 of 0.10 g / 10 min to 0.30 g / 10 min and a Z average molecular weight Mz of 235,000 g / mol to 265,000 g / mol, 238,000 g / mol to 263,000 g / mol, 240,000 g / mol to 261,000 g / mol, or 242,000 g / mol to 259,000 g / mol. In some embodiments, the polyethylene copolymer has a melt index I2 of 0.40 g / 10 min to 0.60 g / 10 min and a Z average molecular weight Mz of 197,500 g / mol to 227,000 g / mol, 200,000 g / mol to 225,000 g / mol, 202,000 g / mol to 223,000 g / mol, or 204,000 g / mol to 221,100 g / mol.

[0039] The polyethylene copolymer may have a number average molecular weight Mn in the range of ((1,027×W)-(18,620×I2)+31,500) g / mol±250 g / mol, ±500 g / mol, or ±1,250 g / mol, wherein W is the weight percent of the comonomer incorporated into the polyethylene copolymer and I2 is provided in g / 10 min. In some embodiments, the polyethylene copolymer has a melt index I2 of 0.10 g / 10 min to 0.30 g / 10 min and a number average molecular weight Mn of 35,200 g / mol to 41,000 g / mol, 36,100 g / mol to 40,000 g / mol, 36,200 g / mol to 39,900 g / mol, or 37,000 g / mol to 39,100 g / mol. In some embodiments, the polyethylene copolymer has a melt index I2 of 0.40 g / 10 min to 0.60 g / 10 min and a number average molecular weight Mn of 29,600 g / mol to 35,400 g / mol, 30,500 g / mol to 34,400 g / mol, 30,600 g / mol to 34,300 g / mol, or 31,500 g / mol to 33,500 g / mol.

[0040] The polyethylene copolymer may have an M of 3.27 to 3.46. w / M n , molecular weight distribution M less than or equal to 2.0z / M w and / or a molecular weight distribution M of 6.42 to 6.95 z / M n In some embodiments, the polyethylene copolymer has a melt index I2 of 0.10 g / 10 min to 0.30 g / 10 min and a molecular weight distribution M of 3.27 to 3.46. w / M n , molecular weight distribution M less than or equal to 2.0 z / M w and / or a molecular weight distribution M of 6.42 to 6.95 z / M n In some embodiments, the polyethylene copolymer has a melt index I2 of 0.40 g / 10 min to 0.60 g / 10 min and a molecular weight distribution M of 3.27 to 3.46. w / M n , molecular weight distribution M less than or equal to 2.0 z / M w and / or a molecular weight distribution M of 6.42 to 6.95 z / M n .

[0041] Polyethylene copolymers may exhibit visual properties according to one or both of the following: 45° gloss greater than or equal to (33.67+(46.67×(I2))) GU, greater than or equal to (38.67+(46.67×(I2))) GU, or greater than or equal to (43.67+(46.67×(I2))) GU, wherein I2 is provided in g / 10 min. In some embodiments, the polyethylene copolymer has a melt index I2 from 0.10 g / 10 min to 0.30 g / 10 min and a 45° gloss greater than or equal to 39 GU, greater than or equal to 44 GU, or greater than or equal to 49 GU. In some embodiments, the polyethylene copolymer has a melt index I2 from 0.40 g / 10 min to 0.60 g / 10 min and a 45° gloss greater than or equal to 53 GU, greater than or equal to 58 GU, or greater than or equal to 63 GU. · A haze of less than or equal to (20.47-(10.33×(I2)))%, less than or equal to (15.47-(10.33×(I2)))%, or less than or equal to (10.47-(10.33×(I2))), wherein I2 is provided in g / 10 min. In some embodiments, the polyethylene copolymer has a melt index I2 of 0.10 g / 10 min to 0.30 g / 10 min and has a haze of less than or equal to 21%, less than or equal to 16%, or less than or equal to 11%. In some embodiments, the polyethylene copolymer has a melt index I2 of 0.40 g / 10 min to 0.60 g / 10 min and a haze of less than or equal to 18%, less than or equal to 13%, or less than or equal to 8%.

[0042] The polyethylene copolymers provided herein exhibit similar comonomer incorporation along all the various chain lengths, with a slightly higher degree of preferential comonomer incorporation on midchain and long chain branches compared to short polymer chains. This phenomenon can be explained using the weight average molecular weight-specific (MW-specific) w -specific) chemical composition distribution index (CCDI). w - Specific CCDI can be considered as: d(comonomer% / d(log M w ).

[0043] M w - Specific comonomer slope index ("CSI") CCDI is calculated by plotting the comonomer % against log (MW) (both measured by GPC with IR detector, as described below) in the region between log (Mw) values ​​of 4.0 to 5.5, and M w -Specific CSI CCDI is taken as the derivative of the comonomer % versus log(MW) plot. More specifically, a plot of comonomer wt% versus log(MW) is fitted to a line, and the slope of the line in the region just described is M w -Specificity M n -M z CCDI.

[0044] M w -Specificity M n -M z CCDI can alternatively be normalized to the short chain branching slope index (SCB / 1000C) by converting the comonomer weight % to short chain branches / 1000 carbons (SCB / 1000C) using the molecular weights of ethylene and the comonomer. w-specific SCB-SI)CCDI. The polyethylene copolymer provided herein may have a lower limit of 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9 or 3.0; and less than or equal to 6.0, 5.9, 5.8, 5.7, 5.6, 5.5, 5.4, 5.3, 5.2, 5.1 or 5.0. w -Specific SCB-SI CCDI, ranges from any of the foregoing lower limits to any of the foregoing upper limits (eg, 2.0 to 6.0, or 3.0 or 5.0) are contemplated herein.

[0045] Although in 4.0≤log(M w )≤5.5 within the range of the above parameters (M w -specific CSI CCDI) is of particular interest, but also useful is the correlation with log(M w ) and instead more generally compares comonomer incorporation (short chain branch content) at high molecular weight chains of a polymer composition to comonomer incorporation (short chain branch content) at low molecular weight chains of a polymer composition, regardless of the length of those chains. For example, a "5-95CSICCDI" can be developed in which the comonomer weight % is compared at two x values ​​in a GPC plot of dWt% / dlog(MW) versus log(MW): (1) at the "5% value", which is the x value for which the area under the GPC curve (from x=0 to x=5% value) is 5% of the total area under the GPC curve (log(MW)). w ) value); and (2) at the "95% value", which is the x value (log(MW) value) at which the area under the GPC curve (x = 0 to x = "95%" value) is 95% of the total area under the GPC curve. 5-95CSI The CCDI can be found as the slope of the linear regression of comonomer weight percent versus log(MW) between these two points (essentially, for 4.0 ≤ log(MW) W )≤5.5, the operation is the same as above, only log(MW)=4.0 is replaced by the log(MW)=5% value, and log(MW)=5.5 is replaced by the log(MW)=95% value). In some embodiments, the 5-95CSI CCDI is normalized to the short chain branching slope index (5-95SCB-SI) CCDI by converting the comonomer weight % to short chain branches / 1000 carbons (SCB / 1000C) using the molecular weights of ethylene and the comonomer.

[0046] The polyethylene composition according to various embodiments can exhibit a lower limit of any one of 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, or 3.0; and a 5-95 SCB-SI CCDI in the range of any one of 6.0, 5.9, 5.8, 5.7, 5.6, 5.5, 5.4, 5.3, 5.2, 5.1, or 5.0, with ranges from any of the foregoing lower limits to any of the foregoing upper limits (e.g., 2.0 to 6.0, or 3.0 or 5.0) being contemplated herein.

[0047] The degree of preferential comonomer incorporation along the low, medium and high molecular weight chains of the polyethylene copolymer can also be characterized by the "Mn-Mz Comonomer Slope Index" (Mn-Mz CSI). The determination of this index is the same as the 5-95 CSI CCDI, except that instead of using log(MW) = "5% value" and log(MW) = "95% value" as the low and high points of the slope determination, log(MW) = log(Mn-Mz) is used. n ) as the low point of the slope determination and log(MW)=log(Mz) as the high point of the slope determination (again with the same M as above) w -Specific CCDI and 5-95CCDI were used in the same manner using linear regression. In some embodiments, the comonomer weight % is converted to short chain branches / 1000 carbons (SCB / 1000C) by using the molecular weights of ethylene and the comonomer. n -M z CSI CCDI is normalized to the short chain branching slope index (M n -M z SCB-SI)CCDI.

[0048] The polyethylene copolymers provided herein can exhibit a lower limit of any one of 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, or 3.0; and less than or equal to M in any range of 8.0, 7.9, 7.8, 7.7, 7.6, 7.5, 7.4, 7.3, 7.2, 7.1, or 7.0. n -M z SCB-SI CCDI, ranges from any of the foregoing lower limits to any of the foregoing upper limits (eg, 2.0 to 8.0, or 3.0 or 7.0) are contemplated herein.

[0049] Linear regression of the comonomer weight % versus Log(MW) plot, regardless of M w -Specific CCDI, 5-95CCDI, Mn-Mz CSI or others, can be performed by any suitable method, for example by using suitable software, such as EXCEL from MicrosoftTM , a linear regression fit of comonomer wt% vs. Log(MW) is performed. For comonomer wt% vs. Log(MW), a linear regression should be performed with a minimum of 30 data points, preferably greater than or equal to 100 data points.

[0050] Another parameter that can be used to demonstrate the similarity of comonomer incorporation along the low, medium, and high molecular weight chains of a polyethylene copolymer is the composition distribution breadth index (CDBI). As noted, the polyethylene copolymer may have a CDBI of 85% or greater, such as 90% or greater. The CDBI is defined as the weight percentage of copolymer molecules having a comonomer content within 50% of the median total molar comonomer content (i.e., within the range of 0.5x the median to 1.5x the median), and is described in U.S. Pat. No. 5,382,630, which is hereby incorporated by reference. The CDBI of a copolymer is readily determined using well-known techniques for isolating individual fractions of a copolymer sample. One such technique is temperature rising elution fractionation (TREF), as described in Wild et al., L Poly. Sci., Poly. Phys. Ed., vol. 20, p. 441 (1982) and U.S. Pat. No. 5,008,204, which are incorporated herein by reference. In some embodiments, the polyethylene copolymer has a CDBI greater than or equal to 70%, 75%, 80%, 85%, or 90%.

[0051] For different embodiments of the present invention, I2, I 21 , MIR, density, g', comonomer percentage, M w 、M z 、M n 、M w / M n 、M z / M w 、M z / M n Any two or more of the foregoing properties of , gloss (45°), haze, CCDI and CDBI may be combined (with each property being within the corresponding range as described above). Aggregation methods

[0052] Polyethylene copolymers can be prepared in a gas phase polymerization system. One or more reactors in series or in parallel can be used. In some embodiments, the catalyst components and activator can be delivered to the reactor separately as a solution or slurry, activated online just before the reactor or in the reactor, or pre-activated and pumped to the reactor as an activated solution or slurry.

[0053] Polymerization can be carried out in (a) single reactor operation, wherein ethylene, olefin comonomer (one or more), catalyst / activator, scavenger and optional modifier are continuously added to a single reactor, or can be carried out in (b) series reactor operation, wherein component is added to each of two or more reactors connected in series. In various embodiments using series reactors, catalyst component can be added to the first reactor of series connection. However, further, catalyst component can be added to multiple reactors, wherein one component is added to the first reactor, and another component is added to other reactors.

[0054] In some embodiments, the polymerization process comprises a gas phase polymerization, particularly a fluidized bed gas phase polymerization. The gas phase polymerization can be carried out in any suitable reactor system, such as a stirred or paddle-type reactor system. See U.S. Pat. Nos. 7,915,357; 8,129,484; 7,202,313; 6,833,417; 6,841,630; 6,989,344; 7,504,463; 7,563,851; and 8,101,691 for a discussion of suitable gas phase fluidized bed polymerization systems, which are well known in the art.

[0055] In such a polymerization process, a gas phase fluidized bed process is carried out by continuously passing a stream containing ethylene and olefin comonomers through a fluidized bed reactor at a speed sufficient to keep a bed of solid particles in suspension under reaction conditions and in the presence of a catalyst composition. A stream containing unreacted ethylene and olefin comonomers (which may be referred to as a "cycle gas" stream) is continuously extracted from the reactor, compressed, cooled, optionally partially or completely condensed, and recycled back to the reactor. The prepared polyethylene copolymer is extracted from the reactor, and replacement ethylene and olefin comonomers are added to the recycle stream. In some embodiments, a gas inert to the catalyst composition and reactants is present in the gas stream.

[0056] The circulating gas may contain an induced condensing agent ("ICA"). An ICA is one or more non-reactive alkanes that are condensable to remove heat of reaction during the polymerization process. In some embodiments, the non-reactive alkanes are selected from C1-C5 alkanes, such as one or more of propane, butane, isobutane, pentane, isopentane, hexane, and isomers and derivatives thereof. In some cases, a mixture of two or more such ICAs may be particularly desirable (e.g., propane and pentane, propane and butane, butane and pentane, etc.).

[0057] In some embodiments, operation of a gas-phase fluidized bed reactor employing ICA may be conducted in a "dry mode" (typically less than 5 mol% total ICA concentration relative to the total circulating gas) as compared to a "condensing" or "condensing" mode with higher ICA concentrations. In some embodiments, the gas-phase process is substantially free of ICA. As noted, it may be desirable to maximize the ICA concentration to obtain faster commercial run times; however, as discussed in conjunction with the following examples, reducing ICA may have a beneficial effect on comonomer distribution. Specifically, according to various embodiments, the polymerization process may employ less than 5 mol% ICA (based on the concentration of the total circulating gas), e.g., 4 mol% or less, 3 mol% or less, 2 mol% or less, 1 mol% or less, or no ICA.

[0058] PCT Publication No. WO 2021 / 221904A1 discloses a density of 0.931 to 0.936 g / cm 3 IP.com Publication No. IPCOM000268060D discloses improved stress crack resistance of polyethylene copolymers with a density of 0.910 to 0.960 g / cm 3 ICA contents ranging from 10 mol% to 18 mol% are used during the gas phase polymerization of ethylene-butene mLLDPE to control rheology and melt strength. In contrast, the examples herein show unexpected reduction in melt viscosity during extrusion of low density, low melt index I2 polyethylene copolymers disclosed herein, particularly ethylene-hexene copolymers, by further limiting the gas phase process to a drying mode as defined above. The examples herein further show reduced melt viscosity during extrusion compared to similar polyethylene copolymers disclosed in IP.com Publication No. IPCOM000266833D.

[0059] As defined herein, the polyethylene copolymer disclosed herein is produced in a dry mode in a gas phase polymerization process, which is suitable for producing a polyethylene composition having a desired 5-95 CCDI. That is, according to certain embodiments in which a polyethylene composition is prepared using a gas phase polymerization process, the concentration of an induced condensing agent (ICA) can be used at least in part to effectively control the chemical composition distribution (i.e., the comonomer distribution along the polymer chain), while also controlling a specific melt index and density. Generally, higher ICA concentrations are preferred, which enables faster production rates (which is of course usually desired); however, this may have a negative impact on the 5-95 CCDI, while directly affecting the melt viscosity. It is surprising and unexpected to find that a slight adjustment of the ICA concentration (e.g., targeting a slightly lower ICA concentration) reduces the melt viscosity while maintaining melt strength. In particular, operating at 5 mol % or less ICA can result in a polyethylene copolymer having a desired 0.3 or greater 5-95 CCDI in addition to having a reduced melt viscosity.

[0060] The polymerization process can be conducted substantially in the absence of catalyst poisons such as moisture, oxygen, carbon monoxide, and acetylene. However, it should be noted that oxygen can be added back into the reactor to alter the polymer structure and the performance characteristics of the polymer.

[0061] In addition, the organometallic compound can be used as a scavenger to remove catalyst poisons, thereby increasing catalyst activity, or for other purposes. Auxiliary agents can also be used or alternatively used in the process. Similarly, hydrogen can be added to affect polymer molecular weight and distribution.

[0062] The amount of hydrogen used in the polymerization process can be the amount necessary to achieve the melt index I2 required for the final polyolefin polymer. For example, the molar ratio of hydrogen to total monomer (H2 / monomer) can be 0.0001 or greater, 0.0005 or greater, or 0.001 or greater. In addition, the molar ratio of hydrogen to total monomer (H2 / monomer) can be 10 or less, 5 or less, 3 or less, or 0.10 or less. The range of the molar ratio of hydrogen to monomer can include any combination of any molar ratio upper limit and any molar ratio lower limit described herein. The amount of hydrogen in the reactor at any time can be up to 5,000ppm, in another embodiment, up to 4,000ppm, in another embodiment, up to 3,000ppm, or 50ppm-5,000ppm, or 50ppm-2,000ppm. The amount of hydrogen in the reactor can be 1 ppm, 50 ppm, or 100 ppm to 400 ppm, 800 ppm, 1,000 ppm, 1,500 ppm or 2,000 ppm, based on weight. In addition, the ratio of hydrogen to total monomer (H2 / monomer) can be 0.00001:1 to 2:1, 0.005:1 to 1.5:1 or 0.0001:1 to 1:1. The pressure of one or more reactors in the gas phase process (single stage or two or more stages) can be 690 kPa (100 psig) to 3,448 kPa (500 psig), 1,379 kPa (200 psig) to 2,759 kPa (400 psig), or 1,724 kPa (250 psig) to 2,414 kPa (350 psig).

[0063] Typically, a continuous cycle is employed in which the first part of the reactor cycle, the cycle gas stream, otherwise known as the recycle stream or fluidizing medium, is heated in the reactor by the heat of polymerization. This heat is removed in the second part of the cycle by a cooling system external to the reactor.

[0064] The reactor pressure can be 100 psig (680 kPag) - 500 psig (3448 kPag), 200 psig (1379 kPag) - 400 psig (2759 kPag), or 250 psig (1724 kPag) - 350 psig (2414 kPag). In some embodiments, the reactor is operated at a temperature of 60°C to 120°C, 60°C to 115°C, 70°C to 110°C, 70°C to 95°C, or 85°C to 95°C.

[0065] The mole % of ethylene can be 25.0-90.0 mole %, or 50.0-90.0 mole %, or 70.0-85.0 mole %, and the ethylene partial pressure is in the range of 75 psia (517 kPa)-300 psia (2069 kPa), or 100-275 psia (689-1894 kPa), or 150-265 psia (1034-1826 kPa), or 200-250 psia (1378-1722 kPa). The ethylene concentration in the reactor may also be in the range of 35-95 mol%, such as in the range of a lower limit of 35, 40, 45, 50 or 55 mol% to an upper limit of 70, 75, 80, 85, 90 or 95 mol%, and further wherein the ethylene mol% is measured based on the total moles of gas in the reactor (including, if present, ethylene and / or comonomer gas and inert gases such as one or more of nitrogen, isopentane or other ICA(s), etc.); as with the vol-ppm hydrogen, for convenience this measurement may be made in the recycle gas outlet rather than in the reactor itself. The comonomer concentration may be in the range of 2.0-6.0 mol%, 2.2-5.6 mol%, 2.4-5.2 mol%, 2.6-4.8 mol%, 2.8-4.4 mol%, 3.0-4.0 mol%.

[0067] Thus, an overall continuous gas phase process for the polymerization of polyethylene may comprise: continuously circulating a feed gas stream containing monomers and inerts to fluidize and agitate a bed of polymer particles, adding a metallocene catalyst to the bed and removing the polymer particles, wherein: a) the catalyst comprises at least one bridged biscyclopentadienyl transition metal and an aluminoxane activator on a common or separate porous support; b) the feed gas is substantially free of Lewis acidic scavengers, and wherein any Lewis acidic scavengers are preferably present in an amount less than 100 ppm by weight of the feed gas; c) the temperature in the bed is no more than 20°C below the melting temperature of the polymer as determined by DSC at an ethylene partial pressure in excess of 60 psig (414 kPaa), and d) the removed polymer particles have a transition metal ash content of less than 500 ppm by weight, a MI of less than 10, a MIR of at least 35, and the polymer has substantially no detectable chain end unsaturation as determined by HNMR.

[0068] The statement that a polymer has substantially no detectable terminal chain unsaturation means that the polymer has less than 0.1 vinyl groups per 1000 carbon atoms in the polymer, such as less than 0.05 vinyl groups per 1000 carbon atoms, for example 0.01 vinyl groups per 1000 carbon atoms or less vinyl unsaturation.

[0069] The method is intended to provide the polyethylene of the present invention via the use of a single catalyst, and the method is independent of the interaction of bridging and unbridged materials. Preferably, the catalyst is substantially free of a metallocene having a pair of π-bonded ligands (e.g., cyclopentadienyl compounds) that are not connected through a covalent bridge, in other words, such a metallocene is not intentionally added to the catalyst, or preferably, such a metallocene cannot be identified in such a catalyst, and the method is substantially using a single metallocene substance comprising a pair of π-bonded ligands, wherein at least one π-bonded ligand has a structure containing at least two cyclic condensed rings (e.g., indenyl rings). Best results can be obtained by using a substantially single metallocene substance comprising a single atom silicon bridge connecting two polynuclear ligands that are π-bonded to a transition metal atom. Catalyst system

[0070] In particular, it is believed that it is desirable to use a catalyst system in which the metallocene has a pair of bridged cyclopentadienyl groups, preferably with a bridge consisting of a single carbon, germanium or silicon atom, to provide an open site on the catalytically active cation. In some embodiments, the metallocene catalyst component is represented by the formula: (C5R′ m )pR″ s (C5R′ m )Q2 in: M is a Group 4, 5, or 6 transition metal; At least one C5R' m is a substituted cyclopentadienyl group; Each R' may be the same or different and is hydrogen, an alkyl, alkenyl, aryl, alkaryl or aralkyl group containing from 1 to 20 carbon atoms or two carbon atoms joined together to form part of one or more rings containing from 4 to 20 carbon atoms, which may be substituted or unsubstituted; R" is to bridge two (C5R' m ) ring containing one or more of carbon, germanium, silicon, phosphorus or nitrogen atoms or a combination thereof; and Each Q may be the same or different and is an aryl, alkyl, alkenyl, alkaryl or aralkyl group containing 1 to 20 carbon atoms, a halogen or an alkoxide.

[0071] In some embodiments, the catalyst is dimethylsilyl-bis-(tetrahydroindenyl)zirconium dichloride (Me2Si(H4Ind)2ZrCl2).

[0072] The activator may be methylaluminoxane, such as U.S. Pat. Nos. 5,324,800; 5,580,939; and 5,633,394 (incorporated herein by reference) (EP-129368) or a non-coordinating anion (EP-277004) described in U.S. Patent Application Serial No. 08 / 133480 (incorporated herein by reference). It is also considered desirable to have substantially no scavengers that may interfere with the reaction between the vinyl terminal unsaturation of the formed polymer and the open active site on the cation. The statements "substantially no scavengers" and "substantially no or no Lewis acid scavengers" mean that less than 100 ppm by weight of such scavengers are present in the feed gas, or preferably, no intentionally added scavengers, such as alkyl aluminum scavengers, are present, other than scavengers that may be present on the support.

[0073] Optimal conditions for producing the polyethylene of the present invention also require steady state polymerisation conditions which are unlikely to be provided by a batch reaction where the amount of catalyst poisons may vary and where the concentration of comonomer may vary in the production of a batch.

[0074] The catalyst is preferably supported on silica, wherein the catalyst is uniformly distributed in the silica pores. Preferably, a relatively small amount of methylaluminoxane should be used, for example an amount to give an Al to transition metal ratio of 400 to 30, especially 200 to 50.

[0075] To obtain the desired melt index ratio, the molar ratio of ethylene and comonomer can be varied, as can the concentration of the comonomer. Control of temperature can help control the MI. Overall monomer partial pressures corresponding to conventional practice for gas phase polymerization of LLDPE can be used. Products

[0076] The polyethylene copolymers described herein may be particularly useful for preparing end-use articles, such as films (e.g., which may be formed by lamination, extrusion, coextrusion, casting and / or blow molding); and may be formed into other articles, such as by blow molding. Film forming methods are well known in the art, and one skilled in the art will readily recognize the use of LLDPE for film preparation. However, it should be noted that the uses of the polyethylene copolymers provided herein may be applications including, but not limited to, stretch hoods, greenhouse films, building linings, blown geomembranes, shrink films, food packaging, and liquid packaging. In some embodiments, the polyethylene copolymers may be used in formulated compositions.

[0077] In some embodiments, the article is a film. The film can be formed by lamination, extrusion or coextrusion. In some embodiments, the film can be embossed. Particularly useful films include those where high melt strength and low melt viscosity are advantageous, such as those produced in large diameter blown film operations. Certain embodiments

[0078] In some embodiments, the polyethylene copolymers, as described herein, comprise ethylene-derived units and units derived from at least one or only one olefin comonomer containing 4 to 8 carbon atoms, and have: a)0.908g / cm 3 Up to 0.916g / cm 3 density; b) a melt index I2 of 0.10 g / 10 min to 0.60 g / 10 min; c) a melt index ratio I greater than or equal to 46.9-(33.3×(I2)) 21 / I2, a melt index ratio I greater than or equal to 51.8-(33.3×(I2)), 52.8-(33.3×(I2)), or greater than or equal to 55.1-(33.3×(I2)) 21 / I2, where I2 is provided in g / 10 min, where I2 is provided in g / 10 min, and d) Optionally, a branching index g'vis of from 0.940 to 0.960.

[0079] In other embodiments, the polyethylene copolymer has one or more of the following properties in addition to the foregoing properties: a) a comonomer content of 9.0 wt.% to 11.0 wt.%; b) the at least one olefin comonomer is butene, hexene or a combination thereof; 1-butene, 1-hexene or a combination thereof; 1-butene or 1-hexene; c) at ((0.0025×W)+(0.0056×*I2)+0.9353)g / cm 3±0.001g / cm 3 The density is in the range of 0.908 g / cm2, wherein W is the weight percent of the comonomer incorporated into the polyethylene copolymer, and I2 is provided in g / 10 min; when the polyethylene copolymer has a melt index I2 of 0.10 g / 10 min to 0.30 g / 10 min, at 0.908 g / cm2 3 Up to 0.915g / cm 3 , 0.909g / cm 3 Up to 0.914g / cm 3 or 0.910g / cm 3 Up to 0.913g / cm 3 or when the polyethylene copolymer has a melt index I2 of 0.40 g / 10 min to 0.60 g / 10 min, at 0.910 g / cm 3 Up to 0.916g / cm 3 、0.911g / cm 3 Up to 0.915g / cm 3 or 0.912g / cm 3 Up to 0.914g / cm 3 within the scope; d) a weight average molecular weight M in the range of ((2,900×W)-(63,500×I2)+110,300) g / mol±1,000 g / mol, ±2,000 g / mol or ±5,000 g / mol w , wherein W is the weight percent of the comonomer incorporated into the polyethylene copolymer, and I2 is provided in g / 10 min; when the polyethylene copolymer has a melt index I2 of 0.10 g / 10 min to 0.30 g / 10 min, at 117,400 g / mol to 135,900 g / mol, 120,300 g / mol to 133,000 g / mol, 120,600 g / mol to 132,700 g / mol or 123,2 or when the polyethylene copolymer has a melt index I2 of 0.40 g / 10 min to 0.60, in the range of 98,300 g / mol to 116,800 g / mol, 101,200 g / mol to 133,900 g / mol, 101,500 g / mol to 113,700 g / mol or 104,100 g / mol to 111,000 g / mol; e) a Z average molecular weight, Mz, in the range of ((2,360×W)-(125,900×I2)+252,000) g / mol±500 g / mol, ±1000 g / mol, or ±2,500 g / mol, wherein W is the weight percent of comonomer incorporated into the polyethylene copolymer, and I2 is provided in g / 10 min; when the polyethylene copolymer has a melt index, I2, of 0.10 g / 10 min to 0.30 g / 10 min, in the range of 235,000 g / mol to 265,000 g / mol, 238,000 g / mol to 263,000 g / mol, g / mol, 240,000 g / mol to 261,000 g / mol or 242,000 g / mol to 259,000 g / mol; or when the polyethylene copolymer has a melt index I2 of 0.40 g / 10 min to 0.60 g / 10 min, in the range of 197,500 g / mol to 227,000 g / mol, 200,000 g / mol to 225,000 g / mol, 202,000 g / mol to 223,000 g / mol or 204,000 g / mol to 221,100 g / mol; f) a number average molecular weight, Mn, in the range of ((1,027×W)-(18,620×I2)+31,500) g / mol±250 g / mol, ±500 g / mol or ±1,250 g / mol, wherein W is the weight percent comonomer incorporated into the polyethylene copolymer, and I2 is provided in g / 10 min; when the polyethylene copolymer has a melt index, I2, of 0.10 g / 10 min to 0.30 g / 10 min, in the range of 35,200 g / mol to 41,000 g / mol, 36,100 g / mol to 40, or when the polyethylene copolymer has a melt index I2 of 0.40 g / 10 min to 0.60 g / 10 min, in the range of 29,600 g / mol to 35,400 g / mol, 30,500 g / mol to 34,400 g / mol, 30,600 g / mol to 34,300 g / mol or 31,500 g / mol to 33,500 g / mol; g) Molecular weight distribution M in the range of 3.27 to 3.46 w / M n ; h) a molecular weight distribution M of less than or equal to 2.0 z / M w ; i) Molecular weight distribution M of 6.42 to 6.95z / M n ; j) a 45° gloss greater than or equal to (33.67+(46.67×(I2))) GU, greater than or equal to (38.67+(46.67×(I2))) GU, or greater than or equal to (43.67+(46.67×(I2))) GU, greater than or equal to 39 GU, greater than or equal to 44 GU, or greater than or equal to 49 GU, when the polyethylene copolymer has a melt index I2 of 0.10 g / 10 min to 0.30 g / 10 min; or greater than or equal to 53 GU, greater than or equal to 58 GU, or greater than or equal to 63 GU, when the polyethylene copolymer has a melt index I2 of 0.40 g / 10 min to 0.60 g / 10 min; k) less than or equal to (20.47 - (10.33 x (I2)))%, less than or equal to (15.47 - (10.33 x (I2)))%, or less than or equal to (10.47 - (10.33 x (I2)))% when the polyethylene copolymer has a melt index I2 of 0.10 g / 10 min to 0.30 g / 10 min; less than or equal to 21%, less than or equal to 16%, or less than or equal to 11% haze; or less than or equal to 18%, less than or equal to 13%, or less than or equal to 8% when the polyethylene copolymer has a melt index I2 of 0.40 g / 10 min to 0.60 g / 10 min; 1) a composition distribution breadth index ("CDBI") greater than or equal to 70%, 75%, 80% or 85%; and m) SCB-SI CCDI greater than or equal to 3.0, which may be further specified as one of the following: i) the lower limit of any one of 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9 or 3.0; and less than or equal to any one of 6.0, 5.9, 5.8, 5.7, 5.6, 5.5, 5.4, 5.3, 5.2, 5.1 or 5.0 w -Specific SCB-SI CCDI, ranges from any of the foregoing lower limits to any of the foregoing upper limits (e.g., 2.0 to 6.0, or 3.0 or 5.0) are contemplated herein; ii) a lower limit of any one of 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, or 3.0; and a 5-95 SCB-SI CCDI less than or equal to any one of 6.0, 5.9, 5.8, 5.7, 5.6, 5.5, 5.4, 5.3, 5.2, 5.1, or 5.0, with ranges from any of the foregoing lower limits to any of the foregoing upper limits contemplated herein (e.g., 2.0 to 6.0, or 3.0 or 5.0); and iii) a lower limit of any one of 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, or 3.0; and a Mn-MzSCB-SI CCDI less than or equal to any one of 8.0, 7.9, 7.8, 7.7, 7.6, 7.5, 7.4, 7.3, 7.2, 7.1, or 7.0, with ranges from any of the foregoing lower limits to any of the foregoing upper limits (e.g., 2.0 to 8.0, or 3.0 or 7.0) contemplated herein.

[0080] In other embodiments of the polyethylene copolymer, the comonomer is hexene, and the polyethylene copolymer is an ethylene-hexene copolymer having: a) a melt index I2 of 0.10 g / 10 min to 0.30 g / 10 min and a melt index ratio I greater than or equal to 45.1, 48.5 or 51.8 21 / I2; or b) a melt index I2 of 0.40 g / 10 min to 0.60 g / 10 min and a melt index ratio I greater than or equal to 35.1, 38.5 or 41.8 21 / I2.

[0081] In some aspects, continuous gas phase processes for producing polyethylene copolymers are provided. The method comprises: a) continuously passing a gaseous stream comprising ethylene and at least one olefin comonomer having from 4 to 8 carbon atoms through a fluidized bed reactor in the presence of a metallocene catalyst under polymerization conditions, wherein the polymerization conditions include an ethylene partial pressure greater than, or equal to, 1300 kPaa and a reactor pressure less than, or equal to, 10,000 kPag; b) extracting the polyethylene copolymer and a stream comprising unreacted ethylene, unreacted comonomer, and an induced condensing agent, wherein the induced condensing agent comprises less than 5 mole percent of the stream; c) cooling the stream comprising unreacted ethylene, unreacted comonomer, and optionally an induced condensing agent to form a cooled stream, wherein the cooled stream is substantially free of a liquid phase; and d) feeding the cooled stream to the fluidized bed reactor along with sufficient additional ethylene and at least one comonomer to replace the ethylene and at least one comonomer polymerized and extracted as the polyethylene copolymer.

[0082] In some embodiments, in addition to the aforementioned attributes of the method, the metallocene catalyst composition is of the formula (C5R′ m ) p R″ s (C5R′ m)Q2 represents, where: M is a Group 4, 5, or 6 transition metal; At least one C5R' m is a substituted cyclopentadienyl group; Each R' may be the same or different and is hydrogen, an alkyl, alkenyl, aryl, alkaryl or aralkyl group containing from 1 to 20 carbon atoms or two carbon atoms joined together to form part of one or more rings containing from 4 to 20 carbon atoms, which may be substituted or unsubstituted; R" is a bridge connecting two (C5R' m ) ring containing one or more of carbon, germanium, silicon, phosphorus or nitrogen atoms or a combination thereof; and Each Q may be the same or different and is an aryl, alkyl, alkenyl, alkaryl or aralkyl group containing 1 to 20 carbon atoms, a halogen or an alkoxy group.

[0083] In other embodiments of the process, the metallocene catalyst is dimethylsilyl-bis-(tetrahydroindenyl)zirconium dichloride (Me2Si(H4Ind)2ZrCl2).

[0084] In other embodiments, in addition to one or more of the foregoing attributes of the process, the at least one olefin comonomer is butene, hexene, or a combination thereof.

[0085] In other embodiments, in addition to one or more of the foregoing attributes of the method, the method is characterized by one or more of the following: a) a reactor bed temperature of 60°C to 120°C, 60°C to 115°C, 70°C to 110°C, 70°C to 95°C, or 85°C to 95°C; b) a reactor pressure of 100 psig (680 kPag) to 500 psig (3448 kPag), 200 psig (1379 kPag) to 400 psig (2759 kPag), or 250 psig (1724 kPag) to 350 psig (2414 kPag); c) a comonomer to ethylene molar ratio of 2% to 6%, 4% to 6% when the comonomer is butene or 1-butene, 3% to 4% when the comonomer is hexene or 1-hexene, or 2% to 3% when the comonomer is octene or 1-octene; d) a mass flow ratio of comonomer to ethylene of 9.5 kg comonomer / kg ethylene to 12.5 kg comonomer / kg ethylene; e) an ethylene partial pressure of greater than or equal to 600 kPaa, greater than or equal to 600 kPaa; greater than or equal to 800 kPaa; greater than or equal to 1000 kPaa; or greater than or equal to 1,200 kPaa; f) an ethylene concentration of 94.5 mol% to 98.0 mol%; 94.5% to 96.0% when the comonomer is butene or 1-butene; 96.0% to 97.5% when the comonomer is hexene or 1-hexene; or 97.0% to 98.0% when the comonomer is octene or 1-octene; g) a ratio of hydrogen to total monomers of 5 ppm / mol to 15 ppm / mol; and h) a hydrogen concentration of from 1 ppm, 50 ppm or 100 ppm to 400 ppm, 800 ppm, 1,000 ppm, 1,500 ppm or 2,000 ppm, based on weight.

[0086] In another aspect, a polyethylene copolymer is produced as the product of any of the above embodiments of the process. DETAILED DESCRIPTION Example

[0087] The following examples are included to illustrate some embodiments of the present invention. It will be appreciated by those skilled in the art that the techniques disclosed in the following examples represent techniques that the inventors have found to work well in implementing the present invention, and therefore can be considered to constitute preferred modes for its practice. However, it will be appreciated by those skilled in the art that many changes may be made in the disclosed specific technical solutions, and similar or similar results may still be obtained, without departing from the spirit and scope of the present invention, according to the present disclosure.

[0088] The above discussion can be further described with reference to the following non-limiting examples. Polyethylene copolymers according to one or more embodiments provided herein were produced in six gas phase polymerization systems (Examples 1-6). The I2, I 21 , MIR, density, g', comonomer percentage, M w 、M z 、M n 、M w / M n 、M z / M w and M z / M n . Test Methods / Polymer Characterization

[0089] Density (g / cm 3 ): Density measurements were made in accordance with ASTM D-1505.

[0090] Dynamic Mechanical Analysis (DMA) rheological measurements (e.g., small strain (10%) oscillatory shear measurements) were performed on a Dynamic Rheometer SR5 stress rotational rheometer with 25 mm diameter parallel plates in frequency sweep mode under a full nitrogen blanket. The polymer samples were appropriately stabilized with antioxidant additives and then inserted into the test fixture for preheating for at least one minute to ensure that the normal force dropped back to zero. All DMA experiments were performed at 10% strain, 0.05 to 100 rad / s, and 190°C. Viscoelastic parameters, including storage modulus (G'), loss modulus (G"), phase angle (δ), complex modulus (G"), and complex viscosity (η*), were determined using Orchestrator software. The value of the storage modulus G' was estimated at 190°C at 500 Pa at a constant value of the loss modulus G" (G' at G" (500 Pa)). This is to characterize and distinguish the viscoelastic properties of the comparative copolymers and the inventive copolymers. This experimental technique provides the opportunity to study various properties of polymer melts, where elastic and viscous moduli (G' and G"), viscosity (η*) and tan δ are generated as a function of dynamic oscillations (frequency) to provide information on the rheological behavior related to the molecular structure.

[0091] Gel Permeation Chromatography ("GPC") 4D Method: a) Unless otherwise stated, molecular weight (M) was determined by using high temperature gel permeation chromatography (Polymer Char GPC-IR) equipped with a multi-channel bandpass filter-based infrared detector IR5, an 18-angle light scattering detector and a viscometer. w 、M n 、M z 、M w / M n distribution and component (moment), comonomer content (C2, C3, C6, etc.), branching index (g') and CCDI (M w -Specificity, 5-95 and M n -M z). Three Agilent PLgel 10-μm mixed-B LS columns were used to provide polymer separation. Aldrich reagent grade 1,2,4-trichlorobenzene ("TCB") with 300ppm antioxidant butylated hydroxytoluene ("BHT") was used as mobile phase. The TCB mixture was filtered through a 0.1-μm Teflon filter and degassed with an online degasser before entering the GPC instrument. The nominal flow rate was 1.0ml / min and the nominal injection volume was 200μl. The entire system including the transfer line, column and detector was loaded in an oven maintained at 145°C. A given amount of polymer sample was weighed and sealed in a standard vial, to which 80-μl flow marker (heptane) was added. After the vial was loaded into the autosampler, the polymer was automatically dissolved in the instrument with 8mL of added TCB solvent. The polymer was dissolved at 160°C, with continuous shaking for about 1 hour for most polyethylene samples or about 2 hours for polypropylene samples. The TCB density used for concentration calculations was 1.463 g / ml at room temperature and 1.284 g / ml at 145°C. The sample solution concentration was 0.2-2.0 mg / ml, with lower concentrations used for higher molecular weight samples. The concentration (c) of each point in the chromatogram was calculated from the IR5 broadband signal intensity (I) minus the baseline using the following equation: c=βI, where β is the mass constant. Mass recovery was calculated from the ratio of the integrated area of ​​the concentration chromatogram to the elution volume and the injected mass was equal to the predicted determined concentration multiplied by the injection loop volume. Conventional molecular weight (IR MW) was determined by combining a universal calibration relationship with a column calibration performed with a series of 700-10 M g / mole monodisperse polystyrene (PS) standard samples. The MW at each elution volume was calculated using the following equation: The variables with the subscript "PS" represent polystyrene, while those without the subscript represent the test sample. PS =0.67 and K PS =0.000175, and α and K for other materials are as calculated and disclosed in the literature (Sun, T. et al., Macromolecules 2001, 34, 6812), except that for the present invention and the appended claims, for linear ethylene polymers, α=0.695 and K=0.000579, for linear propylene polymers, α=0.705 and K=0.0002288, for linear butene polymers, α=0.695 and K=0.000181, and for ethylene-butene copolymers, α is 0.695 and K is 0.000579×(1-0.0087×w2b+0.000018×(w2b) 2), where w2b is the main weight percent of the butene comonomer, for ethylene-hexene copolymers, α is 0.695 and K is 0.000579×(1-0.0075×w2b), where w2b is the main weight percent of the hexene comonomer, and for ethylene-octene copolymers, α is 0.695 and K is 0.000579×(1-0.0077×w2b), where w2b is the main weight percent of the octene comonomer. Unless otherwise stated, concentrations are in g / cm 3 The molecular weight is expressed in g / mole and the intrinsic viscosity (and hence K in the Mark-Houwink equation) is expressed in dL / g. a) The comonomer composition is determined by the ratio of the IR5 detector intensities corresponding to the CH2 and CH3 channels calibrated with a series of PE and PP homo / copolymer standards, the nominal values ​​of which were previously determined by NMR or FTIR. In particular, this provides the methyl groups / 1000 total carbons (CH3 / 1000TC) as a function of molecular weight. The short chain branch ("SCB") content / 1000TC ("SCB / 1000TC") as a function of molecular weight is then calculated as follows: a chain end correction is applied to the CH3 / 1000TC functional groups, assuming that each chain is linear and terminated with a methyl group at each end. The comonomer weight % is then obtained by the following expression, where f is 0.3, 0.4, 0.6, 0.8, etc. for the C3, C4, C6, C8, etc. comonomers, respectively: w2=f*SCB / 1000TC. b) The bulk composition of the polymer from GPC-IR and GPC-4D analysis was obtained by considering all signals of the CH3 and CH2 channels between the integration limits of the concentration chromatogram. First, the following ratio was obtained: c) Then, the same calibration of the ratio of CH2 and CH3 signals as mentioned previously in obtaining CH3 / 1000TC as a function of molecular weight is applied to obtain the bulk CH3 / 1000TC. The bulk methyl chain ends / 1000TC ("bulk CH3 ends / 1000TC") is obtained by weight-averaging the chain end correction over the molecular weight range. Then, w2b=f*main body CH3 / 1000TC, Main body SCB / 1000TC = Main body CH3 / 1000TC - Main body CH3 end / 1000TC, The host SCB / 1000TC was converted into host w2 using the same method as above. d) The LS detector was an 18-angle Wyatt Technology High Temperature DAWN HELEOSII. The LS molecular weight (M) at each point of the chromatogram was determined by analyzing the LS output using the Zimm model of static light scattering (Light Scattering from Polymer Solutions, Huglin, MB, Ed.; Academic Press, 1972.): Here, ΔR(θ) is the excess Rayleigh scattering intensity measured at the scattering angle θ, c is the polymer concentration determined by IR5 analysis, A2 is the second virial coefficient, p(θ) is the shape factor of the monodisperse random coil, and K o is the optical constant of the system: Where N A is Avogadro's constant, (dn / dc) is the refractive index increment of the system. The refractive index of TCB at 145°C and λ=665nm is n=1.500. For the analysis of polyethylene homopolymers, ethylene-hexene copolymers and ethylene-octene copolymers, dn / dc=0.1048 ml / mg and A2=0.0015; for the analysis of ethylene-butene copolymers, dn / dc=0.1048×(1-0.00126×w2) ml / mg and A2=0.0015, where w2 is the weight percentage of butene comonomer. e) The specific viscosity is measured using a high temperature Agilent (or Viscotek Corporation) viscometer having four capillaries arranged in a Wheatstone bridge configuration and two pressure sensors. One sensor measures the total pressure drop across the detector and the other sensor between the two sides of the bridge measures the differential pressure. The specific viscosity η of the solution flowing through the viscometer is s The intrinsic viscosity η at each point in the chromatogram is calculated from their output. s From the equation [η] = η s / c is calculated, where c is the concentration and is determined from the IR5 broadband channel output. The viscosity MW at each point is calculated as M = K PS M aps+1 / [η], where α ps is 0.67, K ps It is 0.000175. f) Calculate the branching index (g') using the output of the GPC-IR5-LS-VIS method as follows vis ). The average intrinsic viscosity of the sample [η] avg Calculated by the following formula: wherein the sum is taken over all chromatogram slices i between the integration limits. g) Branching index g' vis Defined as g' vis =([η] avg ) / (KM v α ), where M v is the viscosity average molecular weight based on the molecular weight determined by LS analysis, and K and α are the K and α of the benchmark linear polymer, which for the purposes of the present invention and the appended claims are: for linear ethylene polymers, α=0.695 and K=0.000579, for linear propylene polymers, α=0.705 and K=0.0002288, for linear butene polymers, α=0.695 and K=0.000181, for ethylene-butene copolymers, α=0.695, K is 0.000579×(1-0.0087w2b+0.000018×(w2b) 2 ), where w2b is the bulk weight percentage of the butene comonomer, for ethylene-hexene copolymers, α is 0.695, K is 0.000579×(1-0.0075×w2b), where w2b is the bulk weight percentage of the hexene comonomer, for ethylene-octene copolymers, α is 0.695, K is 0.000579×(1-0.0077×w2b), where w2b is the bulk weight percentage of the octene comonomer. Unless otherwise stated, concentrations are in g / cm 3 , molecular weight is expressed in g / mole, and intrinsic viscosity (and hence K in the Mark-Houwink equation) is expressed in dL / g. The calculation of w2b values ​​is as discussed above.

[0092] Gloss (Gloss Units ("GU")): Gloss measurements were made at a 45° angle in accordance with ASTM D-2457.

[0093] High load melt index (g / 10min or dg / min): HLMI, also known as I 21 or I 21.6 , characterized by a 21.6 kg load used in the test, measured according to ASTM D-1238, 190°C, 21.6 kg.

[0094] Melt index (g / 10min or dg / min): MI, also known as I2 or I 2.16 , characterized by a 2.16 kg load used in the test, measured according to ASTM D-1238, 190°C, 2.16 kg.

[0095] Small angle oscillatory shear ("SAOS") frequency sweep melt rheology experiments were conducted at 190°C using a 25mm cone (1° and plate configuration) on a MCR301 controlled strain / stress rheometer (Anton Paar GmbH). Sample test discs (25mm diameter, 1mm thickness) were prepared by compression molding pellets (which may be made from fiber samples if necessary) at 190°C using a SchwabenThan laboratory press (200T). The typical cycle for sample preparation was 1 minute without pressure followed by 1.5 minutes under pressure (50 bar) and then cooling between water-cooled plates for 5 minutes. The sample was first balanced at 190°C for 13min to clear any preheating and crystallization history. Next, an angular frequency sweep was performed from 500rad / s to 0.0232rad / s using 6 points / decades and a strain value of 10% was in the linear viscoelastic region determined by the strain sweep experiment. All experiments were conducted in a nitrogen atmosphere to minimize any degradation of the sample during the rheological test. raw materials

[0096] The raw materials used herein are shown in Table 1 below. Table 1 Catalyst preparation

[0097] The catalyst used in each polymerization was a silica-supported metallocene catalyst. The metallocene was dimethylsilylbis(tetrahydroindenyl)zirconium dichloride (Me2Si(H4Ind)2ZrCl2). Methylaluminoxane ("MAO") was the activator / cocatalyst. The preparation of the catalyst followed the procedure as described in U.S. Patent No. 6,476,171, which is incorporated herein by reference for all purposes. 1125 ml of a 30 wt % solution of MAO in toluene (determined by reference to the total aluminum content, which may include unhydrolyzed trimethylaluminum ("TMA")) was charged to a two gallon (7.57 liter) jacketed glass wall reactor equipped with a helical ribbon blender and a helical shaft. 1800 ml of toluene was added and stirred. A suspension of 30.8 g of MCN1 in 320 mL of toluene was cannulated into the reactor. An additional 150 ml of toluene was used to flush solid metallocene crystals into the reactor through a cannula under nitrogen pressure. A color change from colorless to yellow / orange was noted after the metallocene was added to the MAO solution. The mixture was allowed to stir at 69°F (20.6°C) for one hour and then transferred to a four liter Erlenmeyer flask under nitrogen. 899 g of S1 is added to the reactor. Then half of the solution from the 4L Erlenmeyer flask is transferred back to the 2 gallons (7.57 liters) stirred glass reactor. The reaction temperature rises from 70°F (21.1°C) to 100°F (37.8°C) in a five-minute exotherm. The remainder of the solution in the 4 liter Erlenmeyer flask is subsequently added back to the glass reactor and stirred for twenty minutes. Then, toluene (273mL, 238g) is added to dilute the active catalyst slurry, and stirred for another twenty-five minutes. Antistatic agent AS-990 is introduced into the reactor with a conduit and mixed The slurry was mixed for thirty minutes. Solvent removal was initiated by reducing the pressure to less than 18.10 inches of mercury (457 mmHg) while feeding a small stream of nitrogen to the bottom of the reactor and raising the temperature from 74°F (23.3°C) to 142°F (61.1°C) over a period of one hour. Drying was then continued for an additional 9.5 hours at 142°F (61.1°C) to 152°F (66.7°C) and a vacuum of 5 inches to 22 inches Hg (177 to 559 mmHg) to dry the support and yield 1291.4 g of free-flowing active supported catalyst material. Polymer preparation

[0098] Polymerization is carried out in a continuous gas phase fluidized bed reactor. The fluidized bed is composed of polymer particles. Gaseous feed streams of ethylene and hydrogen are mixed with liquid comonomers in a mixing tee arrangement and introduced into a recycle gas line below the reactor bed. ICA (specified in the table below for each embodiment) is added together with ethylene and hydrogen, and is also introduced into a recycle gas line below the reactor bed. The respective flow rates of ethylene, hydrogen and comonomer are controlled to maintain a fixed composition target. The ethylene concentration is controlled to maintain a constant ethylene partial pressure. Hydrogen is controlled to maintain a constant molar ratio of hydrogen to ethylene. The concentrations of all gases are measured by an online gas chromatograph to ensure a relatively constant composition of the recycle gas stream.

[0099] Use purified nitrogen as carrier to inject solid catalyst directly into fluidized bed. Adjust its injection amount to maintain constant production rate of polymer. Maintain the reaction bed of growing polymer particles in fluidized state by continuous flow of supplementary feed and recycle gas through reaction zone. Use 1-3ft / sec (0.3 to 0.9m / sec) of superficial gas velocity to reach this point. Operate reactor under total pressure of about 300psig (2068kPa gauge pressure). In order to maintain constant reactor temperature, continuously adjust the temperature of recycle gas up or down to accommodate any change of heat generation rate caused by polymerization.

[0100] The fluidized bed is maintained at a constant height by withdrawing a portion of the bed at a rate equal to the rate of formation of the granular product. The product is moved semi-continuously into a chamber of fixed volume via a series of valves while being sent back to the reactor. This allows efficient separation of the product while recycling most of the unreacted gas back to the reactor. This product is purged to remove entrained hydrocarbons and treated with a small stream of humid nitrogen to passivate any traces of residual catalyst and co-catalyst. The target conditions for the polymerization process in each example are shown in Table 2.

[0101] Inventive Examples I-1 to I-4 were prepared by dry mode gas phase polymerization. Comparative Examples C-5 to C-8 were prepared by condensed mode gas phase polymerization. Inventive Examples I-1 to I-3 and Comparative Examples C-5 and C7 each had a melt index I2 close to 0.2 g / 10 min. Inventive Example I-4 and Comparative Examples I-6 and I-8 each had a melt index I2 close to 0.5 g / 10 min. Table 2 *ICA target for the present invention is zero, but trace amounts may be present.

[0102] Table 3 shows polymer characterization data for the ethylene-hexene copolymers prepared in Examples I-1 to I-4 and C-5 to C-8. Table 3

[0103] Table 4 shows the M values ​​of the ethylene-hexene copolymers prepared in Examples I-1 to I-4 and C-5 to C-8. w -Specific SCB-SI CCDI. Table 4

[0104] Table 5 shows the 5-95 SCB-SICCDI of the ethylene-hexene copolymers prepared in Examples I-1 to I-4 and C-5 to C-8. Table 5

[0105] Table 6 shows the M values ​​of the ethylene-hexene copolymers prepared in Examples I-1 to I-4 and C-5 to C-8. n -M z SCB-SI CCDI. Table 6

[0106] As shown in Table 3, Examples I-1 to I-3, C-5 and C-7, all of which have a melt index I2 of about 0.2 g / 10 min, show that the drying mode and the condensing mode produce polyethylene copolymers with different molecular structures. Inventive Examples I-1 to I-3 have a slightly lower branching index g'vis than Comparative Examples C-5 and C7. This indicates that the polyethylene copolymer produced in the drying mode has a slightly higher degree of long chain branching than the polyethylene copolymer produced in the condensing mode.

[0107] For polyethylene copolymers with a melt index I2 of about 0.5 g / 10 min, Examples I-4, C-6 and C-8 show the same trend. Inventive Example I-4 has a slightly lower branching index g'vis than Comparative Examples C-6 and C-8. This indicates that polyethylene copolymers with a higher melt index produced in a drying mode have a slightly higher degree of long chain branching than polyethylene copolymers produced in a condensing mode.

[0108] Table 3 also shows that Examples I-1 to I-4 have MIR values ​​within the MIR limits of greater than or equal to (46.9-(33.3×I2)) and / or narrower limits of the MIR disclosed herein. Comparative Examples C-5 and C-6 do not meet both the broadest MIR limits and the required branching index g'vis range, and fall further outside the disclosed narrower MIR limits. In addition, Tables 4-6 highlight the different comonomer distributions, with preferential incorporation of comonomers on distinct medium and high molecular weight chains in the dry mode inventive examples, with much higher CCDIs, regardless of which of the various endpoints are used in the calculations, in comparison to the comparative (condensed mode) examples.

[0109] Figure 1 Gel permeation chromatography ("GPC") traces (IR detector) comparing the molecular weight distribution ("MWD") of inventive Examples I-1 to I-3 and Comparative Example C-5 are shown. Examples I-1 to I-3 and C-5 are ethylene-hexene copolymers having a melt index I2 of about 0.2 g / 10 min. This shows that the MWD of the inventive examples and the comparative examples are substantially equal, whether produced in dry or condensed mode.

[0110] Figure 2 A GPC trace comparing the molecular weight distribution ("MWD") of inventive Example I-4 and comparative Example C-6 is shown. Examples I-4 and C-6 are ethylene-hexene copolymers having a melt index I2 of about 0.5 g / 10 min. This shows that the MWD of the inventive examples and comparative examples are substantially equal, whether produced in dry or condensed mode.

[0111] Figure 3 An overlay of the comonomer distribution versus molecular weight is shown for Inventive Examples I-1 to I-3 and Comparative Examples C-5 and C-7. Similar to Tables 4-6, this shows that Inventive Examples I-1 to I-3 produced in dry mode have higher molecular weight polymer chains (e.g., log M w greater than about 5) have a higher weight percent comonomer. Figure 3 It is further shown that the inventive examples I-1 to I-3 produced in dry mode have lower molecular weight polymer chains (e.g. log M w Less than about 4.5) have a lower weight percent comonomer. This again reinforces the M shown in Table 4 w -Specific SCB-SI CCDI, 5-95 SCB-SI CCDI as shown in Table 5 and M as shown in Table 6 n -M zThis is illustrated by the calculated value of CCDI, where a larger positive CCDI indicates more short chain branching on higher molecular weight molecules.

[0112] Figure 4 An overlay of the comonomer distribution versus molecular weight for Examples I-4, C-6, and C-8 is shown. This also shows that Example I-4 of the invention produced in dry mode has a higher comonomer weight percentage (e.g., log M) for higher molecular weight polymer chains than Comparative Example C-6. w greater than about 5). Figure 4 It is further shown that Example 5 of the present invention produced in dry mode has a lower molecular weight polymer chain (e.g. log M w Less than about 4.5) have a lower comonomer weight percentage. This is again further indicated by the M shown in Table 4. w -Specific SCB-SI CCDI, 5-95 SCB-SI CCDI as shown in Table 5 and M as shown in Table 6 n -M z The calculated values ​​of CCDI are shown, where a larger positive CCDI indicates more short-chain branching on higher molecular weight molecules.

[0113] Figure 5 An overlay of the branching index (g') for Examples I-1 to I-3 of the present invention and Comparative Examples C-5 and C-7 over a limited range of molecular weights is shown. Although the lines for Examples I-1 to I-3 of the present invention are difficult to distinguish, Figure 5 It does appear that the g'vis lines of Examples I-1 to I-3 are lower than the lines of Comparative Examples C-5 and C-7.

[0114] Figure 6 An overlay of the branching index (g') for Example I-4 of the present invention and Comparative Examples C-6 and C-8 over a limited range of molecular weights is shown. Although the lines for Examples I-1 to I-3 of the present invention are difficult to distinguish, Figure 6 It does show that the g'vis line for Example I-4 is lower than the lines for Comparative Examples C-6 and C-8. Membrane preparation

[0115] Film samples were prepared by extruding 1 mil (25.4 μm) monolayer films on an Alpine 2 blown film line. Blown film evaluations of the polymers were conducted on an Alpine blown film line equipped with a 160 mm monolayer die with a 30 mil (762 μm) die gap and a 2.5:1 BUR. The extrusion rate was 300 lb / hr (136 kg / hr).

[0116] Table 7 shows the improved processability of Examples I-1 to I-4 of the present invention achieved by reducing melt viscosity. Comparing the average values ​​of Examples I-1 to I-3 with Example C-5, the polyethylene copolymer produced by dry mode gas phase polymerization disclosed herein shows a 12% reduction in motor load, a 6% reduction in melt pressure before the screen pack, and an 11% reduction in melt pressure after the screen pack for a melt index I2 value of about 0.20 g / 10 min. Although Comparative Example C-7 shows comparable processability to Examples I-1 to I-3 of the present invention, it has a higher density (indicating lower toughness) and a higher g'vis (indicating lower overall long chain branching). In addition, Tables 4-6 show that the CCDI of Examples I-1 to I-3 of the present invention is higher than that of Comparative Examples C-5 and C7.

[0117] Comparing the average values ​​of Inventive Example 1-4 with Comparative Examples C-6 and C-8, the polyethylene copolymer disclosed herein produced by dry mode gas phase polymerization shows a 10% reduction in motor load, an 8% reduction in melt pressure before the screen assembly, and an 11% reduction in melt pressure after the screen assembly for a melt index I2 value of about 0.50 g / 10 min. In addition to having worse processability than Inventive Example 1-4, Comparative Example C-8 also has a higher density (indicating lower toughness) and a higher g'vis (indicating lower overall long chain branching). In addition, Tables 4-6 show that the CCDI of Inventive Example 1-4 is higher than that of Comparative Examples C-6 and C-8. Table 7

[0118] Figure 7 The superposition of the phase angle (δ) of Examples I-1, I-2 and C-5 versus the Van Gurp-Palmen plot of complex modulus is shown. The superposition provides a comparison of Examples I-1 and I-2 of the present invention with Comparative Example C-5. The left portion of the graph of Examples I-1 and I-2 of the present invention is lower than the left portion of the graph of Comparative Example C-5. The right portion of the graph of Examples I-1 and I-2 of the present invention is lower than the right portion of the graph of Comparative Example C-5. Although the inventive sample and the comparable sample both show similar phase angle values ​​(δ) at low complex modulus (G*), the phase angle values ​​in the case of the invention show a more dramatic decay compared to the comparable sample, as well as an increase in G* before the steady state. These differences suggest slightly more long chain branching in the examples of the present invention. This will provide greater bubble stability and improved processability during film blowing.

[0119] Figure 8The superposition diagram of the phase angle (δ) of Example I-4 and C-6 versus the van Gurp-Palmen plot of complex modulus is shown. The superposition diagram provides a comparison of Example I-4 of the present invention and Comparative Example C-6. The left portion of the graph of Example I-4 of the present invention is lower than the left portion of the graph of Comparative Example C-6. The right portion of the graph of Example I-4 of the present invention is lower than the right portion of the graph of Comparative Example C-6. Although the inventive sample and the comparable sample both show similar phase angle values ​​(δ) at low complex modulus (G*), the phase angle values ​​in the case of the invention show a more rapid decay compared to the comparable sample, as well as an increase in G* before the steady state. These differences suggest slightly more long chain branching in the present embodiment. This will provide greater bubble stability and improved processability during film blowing.

[0120] As shown in Table 4, subtle differences in molecular structure have a significant impact on extrudability during blown film manufacturing. It should be noted that while the MIR of the polymer is affected by reactor temperature (see Tables 2 and 3), samples produced in dry mode consistently exhibited better extrudability than samples produced in condensing mode, thus allowing the end user to potentially run at higher output rates and / or lower energy consumption. Although the present invention and its advantages have been described in detail, it should be understood that various changes, substitutions and modifications can be made here without departing from the spirit and scope of the present invention as defined by the appended claims. The scope of various features and attributes disclosed herein is listed as a sequentially narrowed scope. However, it should be understood that any lower endpoint of any scope can be paired with any upper endpoint of the same characteristic or attribute, and such pairing is also intended to be disclosed herein. All patents, test procedures and other documents cited in this application are fully incorporated herein by reference, reaching all rights allowing such incorporation. In addition, the scope of the present application is not intended to be limited to the specific embodiments of the process, machine, film structure, composition, device, method and / or step described in the specification. As those of ordinary skill in the art will readily understand from the disclosure of the present invention, according to the present invention, it is possible to utilize the process, machine, film structure, composition, device, method and / or step of the layer that currently exists or is developed later to perform the same function as the corresponding embodiment described herein or to achieve substantially the same result. Therefore, the appended claims are intended to include these processes, machines, film structures, composition, device, method and / or steps in their scope.

Claims

1. A polyethylene copolymer comprising ethylene-derived units and units derived from at least one olefin comonomer containing 4 to 8 carbon atoms and having: a)0.908g / cm 3 Up to 0.916g / cm 3 density; b) a melt index I2 of 0.10 g / 10 min to 0.60 g / 10 min; and c) a melt index ratio I greater than or equal to 46.9-(33.3×(I2)) 21 / I2, where I2 is provided in g / 10min.

2. The polyethylene copolymer of claim 1, wherein the melt index is greater than 1 21 / I2 is greater than or equal to 55.1-(33.3×(I2)).

3. The polyethylene copolymer of claim 1 or claim 2, further having a branching index g'vis of 0.940 to 0.

960.

4. The polyethylene copolymer of claim 1 or any one of claims 2-3, further having ((0.0025×W)+(0.0056×*I2)+0.9353) g / cm 3 ±0.001g / cm 3 Where W is the weight percent of comonomer incorporated into the polyethylene copolymer.

5. The polyethylene copolymer of claim 1 or any one of claims 2-4, wherein the at least one olefin comonomer is butene, hexene, or a combination thereof, and further wherein the comonomer content of the polyethylene copolymer is in the range of 9.0 wt% to 11.0 wt%.

6. The polyethylene copolymer of claim 1 or any one of claims 2-5, further comprising one or more of the following: a) Weight average molecular weight M in the range of ((2,900×W)-(63,500×I2)+110,300) g / mol±2,000 g / mol w ; b) Z average molecular weight M in the range of ((2,360×W)-(125,900×I2)+252,000) g / mol±1,000 g / mol z ;and c) Number average molecular weight M in the range of (1,027×W)-(18,620×I2)+31,500) g / mol±500 g / mol n .

7. The polyethylene copolymer of claim 6, further comprising one or more of the following: a) Molecular weight distribution M in the range of 3.27 to 3.46 w / M n ; b) a molecular weight distribution M of less than or equal to 2.0 z / M w ;and c) Molecular weight distribution M in the range of 6.42 to 6.95 z / M n .

8. The polyethylene copolymer of claim 1 or any one of claims 2 to 7, further comprising: a) a composition distribution breadth index ("CDBI") greater than or equal to 85%; b) a Short Chain Branching Slope Index Chemical Composition Distribution Index ("SCB-SI CCDI") greater than or equal to 3.0; or c) combinations thereof.

9. The polyethylene copolymer of claim 1 or any one of claims 2 to 8, further comprising: a) 45° gloss greater than or equal to (33.67+(46.67×(I2))) GU; b) a haze less than or equal to (20.47 - (10.33 x (I2))) %; or c) combinations thereof.

10. The polyethylene copolymer of claim 1 or any one of claims 2-9, wherein the at least one comonomer is hexene, the polyethylene copolymer having: a) a melt index I2 of 0.10 g / 10 min to 0.30 g / 10 min; and b) a melt index ratio I greater than or equal to 45.1 21 / I2.

11. The polyethylene copolymer of claim 1 or any one of claims 2-9, wherein the at least one comonomer is hexene, the polyethylene copolymer having: a) a melt index I2 of 0.40 g / 10 min to 0.60 g / 10 min; and b) a melt index ratio I greater than or equal to 35.1 21 / I2.

12. A continuous gas phase process for producing a polyethylene copolymer, said process comprising: a) continuously passing a gaseous stream comprising ethylene and at least one olefin comonomer having from 4 to 8 carbon atoms through a fluidized bed reactor in the presence of a metallocene catalyst under polymerization conditions, wherein the polymerization conditions include an ethylene partial pressure of greater than, or equal to, 600 kPa and a reactor pressure of less than, or equal to, 10,000 kPa; b) extracting the polyethylene copolymer and a stream comprising unreacted ethylene, unreacted comonomer, and optionally an induced condensing agent, wherein the induced condensing agent comprises less than 5 mole percent of the stream; c) cooling the stream comprising unreacted ethylene, unreacted comonomer, and an induced condensing agent to form a cooled stream, wherein the cooled stream is substantially free of a liquid phase; and d) feeding the cooled stream to the fluidized bed reactor along with sufficient additional ethylene and at least one comonomer to replace the ethylene and at least one comonomer polymerized and extracted as the polyethylene copolymer.

13. The method of claim 12, wherein the metallocene catalyst composition is represented by the formula: (C5R′ m ) p R″ s (C5R′ m )Q2 in: M is a Group 4, 5, or 6 transition metal; At least one C5R' m is a substituted cyclopentadienyl group; Each R' may be the same or different and is hydrogen, an alkyl, alkenyl, aryl, alkaryl or aralkyl group containing from 1 to 20 carbon atoms or two carbon atoms joined together to form part of one or more rings containing from 4 to 20 carbon atoms, which may be substituted or unsubstituted; R" is a bridge connecting two (C5R' m ) ring containing carbon, germanium, silicon, phosphorus or nitrogen atoms, or one or more or a combination thereof; and Each Q may be the same or different and is an aryl, alkyl, alkenyl, alkaryl or aralkyl group containing 1 to 20 carbon atoms, a halogen or an alkoxy group.

14. The process of claim 13, wherein the metallocene catalyst composition is dimethylsilyl-bis-(tetrahydroindenyl)zirconium dichloride (Me2Si(H4Ind)2ZrCl2).

15. The process of claim 12 or any one of claims 13-14, wherein the at least one olefin comonomer is butene, hexene, or a combination thereof.

16. The method of claim 12 or any one of claims 13-15, further comprising one or more of the following: a) a reactor bed temperature of 60°C to 120°C; b) a reactor pressure of 680 kPag to 3448 kPag; c) a comonomer to ethylene molar ratio of 2% to 6%; d) a mass flow ratio of comonomer to ethylene of 9.5 kg comonomer / kg ethylene to 12.5 kg comonomer / kg ethylene; e) an ethylene partial pressure greater than or equal to 1,200 kPaa; f) an ethylene concentration of 94.5 mol % to 98.0 mol %; g) a ratio of hydrogen to ethylene of from 5 ppm / mol to 15 ppm / mol; and h) A hydrogen concentration of 1 ppm to 2,000 ppm.

17. The process of claim 12 or any one of claims 13-16, wherein the polyethylene copolymer comprises ethylene-derived units and units derived from at least one olefin comonomer containing 4 to 8 carbon atoms, and has: a)0.908g / cm 3 Up to 0.916g / cm 3 density; b) a melt index I2 of 0.10 g / 10 min to 0.60 g / 10 min; c) a melt index ratio I greater than or equal to 46.9-(33.3×(I2)) 21 / I2, where I2 is provided in g / 10min; and d) a branching index g'vis of 0.940 to 0.

960.

18. The method of claim 17, wherein the at least one comonomer is hexene and the polyethylene copolymer has: a) a melt index I2 of 0.10 g / 10 min to 0.30 g / 10 min; and b) a melt index ratio I greater than or equal to 45.1 21 / I2.

19. The method of claim 17, wherein the at least one comonomer is hexene and the polyethylene copolymer has: a) a melt index I2 of 0.40 g / 10 min to 0.60 g / 10 min; and b) a melt index ratio I greater than or equal to 35.1 21 / I2.

20. A polyethylene copolymer produced by the process of claim 13.

Citation Information

Patent Citations

  • Process and catalyst for polyolefin density and molecular weight control

    EP0129368A1

  • Catalysts, method of preparing these catalysts and method of using said catalysts

    EP0277004A1

  • Method for determining the compositional distribution of a crystalline copolymer

    US5008204A

  • Process and catalyst for polyolefin density and molecular weight control

    US5324800A

  • Linear ethylene interpolymer blends of interpolymers having narrow molecular weight and composition distribution

    US5382630A